2022
DOI: 10.1021/acs.jnatprod.2c00894
|View full text |Cite
|
Sign up to set email alerts
|

Daphnepedunins A–F, Anti-HIV Macrocyclic Daphnane Orthoester Diterpenoids from Daphne pedunculata

Abstract: From the whole plant of Daphne pedunculata, 12 macrocyclic daphnane diterpenoids, including six new compounds, daphnepedunins A−F (1−4, 9, and 10), were isolated. Their structures were elucidated by physiochemical and spectroscopic data analysis, the modified Mosher's method, and X-ray crystallography. The isolated compounds were evaluated for anti-HIV activity against HIV-1 infection in MT4 cells and showed significant anti-HIV activity with IC 50 values of 36.3−994 nM. A consideration of the anti-HIV activit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 22 publications
2
8
0
1
Order By: Relevance
“…A recent study reported the isolation of daphnepedunin A ( DA ). [ 52 ] In their study, DA displayed a therapeutic activity against HIV, but this activity was much weaker than the positive control gnidimacrin, and its underlying pharmacological mechanism remained untested. For inhibiting the fibrotic protein expression in activated renal fibroblasts and kidney fibrosis mouse models, DA exerted a beneficial effect, superior to that of PFD, a small molecule compound that has been approved to treat human idiopathic pulmonary fibrosis, and extensively explored in clinical trials for the treatment of kidney fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study reported the isolation of daphnepedunin A ( DA ). [ 52 ] In their study, DA displayed a therapeutic activity against HIV, but this activity was much weaker than the positive control gnidimacrin, and its underlying pharmacological mechanism remained untested. For inhibiting the fibrotic protein expression in activated renal fibroblasts and kidney fibrosis mouse models, DA exerted a beneficial effect, superior to that of PFD, a small molecule compound that has been approved to treat human idiopathic pulmonary fibrosis, and extensively explored in clinical trials for the treatment of kidney fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…δ C 172–174 are observed in the 13 C-NMR spectra (Fig. 10 ) [ 18 , 19 , 35 38 ]. In the B-ring, most daphnanes ( 7 , 9 , 11 , and 12 ) have an α-oriented 6,7-epoxy group, with the oxymethine carbon resonance of C-7 observed at ca.…”
Section: Structure Determinationmentioning
confidence: 99%
“…Determination of the relative configuration of alkyl groups branching on the macrocyclic ring part is a key point in the structural elucidation of MDOs, requiring careful analysis of NOE (or ROE). Recently, we reported a facile way to assign the relative configuration of the methyl group at C-9′ in the C 10 aliphatic chain-type MDO by observing the chemical shift of C-10 or C-10′ [ 35 ].
Fig.
…”
Section: Structure Determinationmentioning
confidence: 99%
“…, 707 (16), 689 (19), 671 (57), 653 (23), 643 (20), 629 (21), 625 (23), 611 (28), 593 (18), 583 (17), 549 (72), 531 (17), 521 (22), 507 (29), 503 (20), 489 (73), 479 (22), 471 (54), 461 (68), 453 (22), 443 (56), 425 (18), 415 (19), 375 (15), 363 (29), 307 (37), 291 (26), 279 (16), 221 (25) (10), 343 (23), 325 (20), 315 (6), 313 (5), 307 (10), 297 (16), 295 (5), 279 (11), 271 (7), 269 (6), 267 (8), 253 (15), 207 (100), 203 (5), 107 (8), 95 (8), 81 (6) wikstroelide M [14] 529 (35), 511 (30), 501 (32), 493 (27), 483 (59), 467 (29), 465 (64), 449 (21), 447 (29), 439…”
Section: Detection Of Daphnane Diterpenoids In W Indica By Lc-ms/msunclassified
“…During our ongoing research aimed at discovering biological diterpenoids from plants of the Thymelaeaceae family [5,20,29,30], this study comprehensively examined and identified daphnane diterpenoids in the stems of W. indica using LC-MS/MS analysis.…”
Section: Introductionmentioning
confidence: 99%